Quality Improvement Strategy for Professional Master's Degree Postgraduates based on Key Link Detection - Du, Le (Transactions on Social Science, Education and Humanities Research, 2023)
In order to improve the training quality of professional masters, a Q-GERT network model based on the training process of professional masters was constructed, the key node measurement coefficient was used to quantitatively identify the key influencing factors, and the training process of economic and management professional masters in a provincial university of Jiangsu Province was taken as an example for empirical analysis. The results show that the key factors affecting the quality of economic and management master training are the practice teaching, the guidance of tutors and the establishment of a sound quality evaluation system. To improve the training quality of professional master talents, we should start from the construction of practical ability training system, the implementation of "double tutor system" and the establishment and improvement of practical ability oriented quality evaluation standards, and monitor the training dynamic in real time, and continuously improve the quality of training.